2008
DOI: 10.4049/jimmunol.181.11.7617
|View full text |Cite
|
Sign up to set email alerts
|

The Erk2 MAPK Regulates CD8 T Cell Proliferation and Survival

Abstract: The magnitude of T cell responses is determined by proliferation and survival decisions made by the responding cells. We now demonstrate that the Erk MAPK pathway plays a critical role in these cell fate decisions within CD8 T cells. While Erk1 is dispensable for all aspects of CD8 T cell activation, Erk2 is required for the proliferation of CD8 T cells activated in the absence of costimulation. Surprisingly, Erk2 is not required for proliferation following the addition of a costimulatory signal in vitro, or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
151
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 65 publications
18
151
1
1
Order By: Relevance
“…Considering the defective NOD nTreg TCR repertoire as an independent phenotype could be consistent with involvement of Lck. Indeed, Lck is a key component of TCR signal transduction in contrast with ERK, which is not required for T cell activation (42). However, because proliferation in CD3/CD28-stimulated NOD T cells is not decreased (7), we consider that alterations in this gene are unlikely to underlie any of the defects reported in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Considering the defective NOD nTreg TCR repertoire as an independent phenotype could be consistent with involvement of Lck. Indeed, Lck is a key component of TCR signal transduction in contrast with ERK, which is not required for T cell activation (42). However, because proliferation in CD3/CD28-stimulated NOD T cells is not decreased (7), we consider that alterations in this gene are unlikely to underlie any of the defects reported in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Although the Fas-mediated apoptosis after c-FLIP siRNA inhibition in B16 cells showed no difference compared with control siRNA, we cannot exclude that c-FLIP plays a role in the Fas resistance of B16 cells, because the effect of c-FLIP knock down is mild, and the expression of c-FLIP decreases only ∼50%. It was reported that activation of the ERK pathway and subsequent induction of antiapoptotic proteins, such as Bcl-2, play important roles in the survival of CD8 + T and NK cells (44,45) In B16 tumor cells stimulated by FasL + EXO, we found that Bcl-2 was upregulated after EXO stimulation, and specific inhibitors of ERK and NF-kB activation could decrease the expression of Bcl-2. But there was no increasing apoptosis in the B16 cells treated with Bcl-2 inhibitor compared with the group treated with DMSO or control, which suggests that Bcl-2 may not be involved in the Fas resistance of B16 tumor cells induced by FasL-expressed EXO (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Although Erk2 is known to play a crucial role in T-cell development and activation, 9,11 the role of Erk1 in T-lineage cells remains controversial. 4,5,9,11 Importantly, the development and maintenance of Erk1-deficient T cells in an Erk1-sufficient background has never been examined. Our data suggest that both Erk1 and Erk2 are necessary for normal T-cell development/maintenance in vivo.…”
Section: Erk2mentioning
confidence: 99%
“…Genetic experiments argued that Erk1 is required for T-cell development, 4 although this observation is controversial. 5,9,11 T-cell-specific deletion of Erk2 also leads to defective T-lymphocyte maturation, suggesting that in some cellular contexts, ERK1 cannot compensate for ERK2. 9 By contrast, either Erk1 or Erk2 is sufficient for normal B-cell development, 12 although this process is markedly impaired in Erk1/2 doubly-deficient B cells.…”
Section: Introductionmentioning
confidence: 99%